The Relationship Between Emotional Regulation, Resilience And Quarter Life Crisis In Final Year Student - Larasati, Nurul Afifah; Suroso; Pratitis, Niken Titi (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Emerging adulthood is the transition period from adolescence to adulthood, happening between the ages of 18 and 29. During this stage, people face many challenges, such as learning new skills and adapting to changes, especially final-year university students. The emotional struggle experienced in this phase is called the quarter-life crisis. This study aims to understand the relationship between emotion regulation, resilience, and the quarter-life crisis among final-year university students in Pekanbaru. Data were collected through an online questionnaire from 155 students and analyzed using multiple regression analysis. The results show that emotion regulation and resilience are connected to the quarter-life crisis (F = 51.020, p < 0.05). Individually, emotion regulation (t = -4.321, p < 0.05) and resilience (t = -4.129, p < 0.05) have a negative relationship with the quarter-life crisis. This means that the better a person can regulate emotions and be resilient, the lower their chances of experiencing a quarter-life crisis.